Emblems from the Heart: The Reception of the Cor Iesu Amanti Sacrum Engravings Series in Polish and Netherlandish 17th-Century Manuscripts - Grześkowiak, Radosław; Hulsenboom, Paul (Werkwinkel, 2015)
The Cor Iesu amanti sacrum, a series of engravings made by Anton II Wierix around the year 1600, became one of the most important series of religious emblems from the 17th and 18th centuries. The engravings’ printed reception is well known: there are numerous graphical copies, as well as books written on the basis of the emblems, starting with the work by the French Jesuit Étienne Luzvic, entitled Le cœur devot throsne royal de Iesus pacifique Salomon, from 1626. The article discusses the handwritten reception of the series, which until now has remained virtually uninvestigated. The authors analyze five works of literature, preserved in Polish and Netherlandish 17th-century manuscripts and inspired by the engravings from the Cor Iesu amanti sacrum: Het herte Jesu by an anonymous Netherlandish protestant (a manuscript from Tilburg), Opofferingh van het herte aan den Bruijdegom Iesus Christus by the Netherlandish scientist and doctor Jan Swammerdam (a manuscript from Ghent), and three untitled Polish versions: a poetical collection by the Jesuit Mikołaj Mieleszko, dedicated to the Duchess Katarzyna Radziwiłł in 1657 (a manuscript from Saint-Petersburg) and two different works preserved in monastic libraries (manuscripts from Imbramowice and Stary Sącz).